Perlindungan Hukum Terhadap Tanah Masyarakat Hukum Adat Di Kawasan Hutan Lindung Negeri Masihulan Kecamatan Seram Utara Kabupaten Maluku Tengah - Meske Patalatu; Jenny Kristiana Matuankotta; Yosia Hetharie (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Land and forests are the basis of people's prosperity and welfare.Methods of the Research: The research method used is normative juridical research type. The problem approach used is the statutory approach, the conceptual approach, and the case approach. The legal materials used are primary legal materials, secondary legal materials and tertiary materials. Procedures and collection of law and management and analysis of legal materials are then analyzed by way of description with qualitative methods.Results of the Research: The results of the study show that the mechanisms and procedures for the Protection of Land Rights of Indigenous Law Communities in the Protected Forest Area of the Masihulan State, North Seram District, Central Maluku Regency have been neglected by the existence of protected forests or the existence of a national park, even though it is through this land that the indigenous peoples of the Masihulan Country are passed down from generation to generation. Generations can take advantage of the natural resources that exist in customary forests such as plants and animals in customary forests for their survival and daily life. The rights of the customary law community, in this case the land including their customary forest, have not received legal protection as it should be in accordance with the mandate of the 1945 Constitution of the Republic of Indonesia Article 18B paragraph (2) and other laws and regulations